Peran Interaksi Simbolik Dalam Perencanaan Komunikasi Pemasaran ( Studi Kasus Strogen Indonesia ) - Gerry Hadi Putra; Muhammad Adi Pribadi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
In the midst of the rise of communication through digital media and the internet, it is easier to disseminate information, so many companies use the internet as a means of marketing communication. One brand that uses the Internet as a marketing communication medium is Strogen Indonesia. Strogen is a private company that focuses on selling smart home appliances products that are present with the latest technology and have the aim of helping users do their daily homework. In carrying out marketing communications, Strogen Indonesia focuses on sharing attractive visuals of its products as a symbol that can be widely accepted by consumers. Strogen Indonesia shares the visuals of its products through various media such as company websites, Instagram, to Youtube. In addition, Strogen Indonesia also tries to listen to consumers and makes it easier for consumers to communicate by having various social media that actively answer various questions and complaints from customers to achieve the best customer service. Researchers want to focus on the title of the thesis